(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Talikuran Village, Kawangkoan District, was the one of the culinary centers in Minahasa Regency. This area has many restaurants, starting from Minahasa restaurants with Ragey (minahasan satay from pork) as a main menu and restaurants with Biapong (minahasan bakpao with pork) as a main menu. The problem found with partners was a lack of understanding of sanitation and hygiene in restaurants during the Covid-19 pandemic. The solution offered is to carry out health education activities about sanitation and hygiene in restaurants during the Covid-19 pandemic. The achievement target is increasing the knowledge of restaurant workers about restaurant sanitation and hygiene during the Covid-19 pandemic. This activity is planned to be carried out in stages. This health promotion activity was carried out 1 (one) time. Overall this activity takes about 6 (six) months. The results of the health promotion showed an increase in the knowledge of the restaurant workers.